Legal Protection and Liability of Business Actors for Lost Packages in Freight Forwarding Services Through PT. JNE Kediri Region - MA'RUF, ALI; SUSHANTY, VERA RIMBAWANI (Jurnal Independent, 2022)
AbstractIn the current digital era, a business that has a good opportunity is the field of expeditionservices. PT. Tiki Lintas Nugraha Ekakurir (JNE) is a privately owned freight forwardingcompany that has many customers. There is a relationship between the delivery serviceprovider and the service user, sometimes there are problems such as loss of goods experiencedby consumers. As a result, consumers do not get their rights, namely the package sent to thedestination. With this, legal protection and the responsibility of business actors are needed toconsumers as users of expedition services.The research method used in solving this problem is normative empirical research. Bymaking direct observations of the liability of service providers and legal protection forconsumers for the loss of goods with a case study at PT. JNE Kediri branch. The statuteapproach is used to obtain legal rules that guarantee legal protection for consumers at PT. JNEKediri.Based on the legal rules for consumer protection written in the Criminal Code, theCommercial Code, the Postal Law and the Consumer Protection Law, it is stated that businessactors have an obligation to maintain the security of packages during the delivery process totheir destination. If the package is lost, the business actor is obliged to compensate theconsumer for the loss. Compensation given by replacing according to the lost package or in theform of money whose nominal value is the same as the lost package. PT. JNE Kediri prioritizesthe interests of consumers, especially in the case of lost packages and seeks a family settlementby taking the negotiation route. As a business actor PT. JNE is obliged to bear the loss of thepackage due to negligence or error by providing compensation in the form of compensation upto 10 times the value of the shipping cost if the package is not insured.